DIGITAL MARKETING, CYBERCRIME, AND ISLAMIC BUSINESS ETHICS A CASE STUDY IN INDONESIA - Rizky, Farid Al; Mualimin, Jaya; Nurhasanah, Siti (AB-JOIEC: Al-Bahjah Journal of Islamic Economics, 2023)
This study aims to explore digital marketing in-depth, and cybercrime in the business sector in Indonesia. This study investigates the important contribution of Islamic business ethics in anticipating cybercrimes in the digital economy in Indonesia. The impact of digital marketing and cybercrime incidents on the business sector needs to be investigated further in order to minimize the occurrence of cybercrime, such as in e-Commerce Shopee, Tokopedia and some of them by using a qualitative approach and case studies. One of the triggers for incidents of cybercrime is due to the use of digital marketing which has now gone global, but self-awareness is weak so it is necessary to internalize the values of Islamic business ethics in order to prevent it from within oneself. This study focuses on the economic and business sectors so that the findings can be generalized to other sectors. Then, a descriptive analysis study was used to explore case by case to help categorize research findings. Awareness of information and communication technology security has received less attention due to the proliferation of digital technology innovations which have implications for cybercrimes in the economic and business sectors. Therefore, it is important for business people (users, consumers, and society) to realize that business ethical values are very important in achieving success, not just materially but non-materially. This study describes in depth the benefits of digital marketing on the one hand, and on the other hand the negative impact that results in cybercrime. This study also raises awareness among business people about the importance of Islamic business ethics in the economic and business sectors.